2020
DOI: 10.1002/cctc.202000755
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodesulfurization Properties of Nickel Phosphide on Boron‐treated Alumina Supports

Abstract: The deep hydrodesulfurization (HDS) properties of nickel phosphide (Ni 2 P) on boron-modified alumina (xBÀ Al 2 O 3) supports having different B contents have been investigated. Ni 2 P precursors were prepared on the xBÀ Al 2 O 3 supports using hypophosphite (-hypo) or phosphate (-phos) as the P source and were subsequently reduced in flowing hydrogen. The 4,6dimethyldibenzothiophene HDS activities and turnover frequencies of the Ni 2 P/xBÀ Al 2 O 3 catalysts showed a strong dependence on B loading, with a max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…[102,123,[125][126][127][128][129][130] Another important class of HDS catalysts, gaining fast research interests and touted to be a serious alternative to the transition metal sulfides is transition metal phosphides (MP or M 2 P). [131][132][133][134][135][136][137][138][139][140][141][142][143][144] This popularity and research acceptability is due to their intrinsic catalytic performance during HDS reaction that is well compared to the conventional sulfided Ni(Co)Mo(W). In addition, these catalysts series are easily prepared from the corresponding oxides and chlorides, and possessed dual properties of metals and ceramics with excellent thermal and chemical stability, as well as good conductors of heat.…”
Section: Active Phasementioning
confidence: 99%
“…[102,123,[125][126][127][128][129][130] Another important class of HDS catalysts, gaining fast research interests and touted to be a serious alternative to the transition metal sulfides is transition metal phosphides (MP or M 2 P). [131][132][133][134][135][136][137][138][139][140][141][142][143][144] This popularity and research acceptability is due to their intrinsic catalytic performance during HDS reaction that is well compared to the conventional sulfided Ni(Co)Mo(W). In addition, these catalysts series are easily prepared from the corresponding oxides and chlorides, and possessed dual properties of metals and ceramics with excellent thermal and chemical stability, as well as good conductors of heat.…”
Section: Active Phasementioning
confidence: 99%
“…Sulfur-free supported carbide, nitride, or phosphide catalysts (MoCx, MoNx, or MoPx) appear to be better candidates for co-processing than conventional ones due to the fact of no sulfur needed to maintain its activity. Moreover, several studies have reported significant catalyst activity in the case of triglycerides processing.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Ni 2 P with small particle size possessed higher hydrogenation activity. 27 , 29 33 Oyama et al reported that there were two types of sites in Ni 2 P, Ni(1) sites with tetrahedral coordination and Ni(2) sites with square pyramidal coordination. Moreover, they found that Ni(2) sites were beneficial to the hydrogenation reaction, and there were more Ni(2) sites as the Ni 2 P particle size became smaller.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 32 Bussell et al investigated the difference in using phosphate and hypophosphite for Ni 2 P/Al 2 O 3 catalysts and found that hypophosphite-based Ni 2 P/B-Al 2 O 3 with smaller Ni 2 P particle size exhibited higher HDS activities. 33 As we all know, the particle size of Ni 2 P is greatly related to the preparation methods. Normally, Ni 2 P catalysts are prepared by a programmed temperature reduction method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation